Global Foresight for Food and Agriculture Tool - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
This version of the tool has been introduced to the public with a formal launch event. It can be used by researchers and policy-makers to explore the impact of agricultural investment options, on agricultural productivity and food security.